ANALISIS KEMAMPUAN SPASIAL SISWA MELALUI TEORI BELAJAR VAN HIELE PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Dedi Kusnadi; Mardyanto Barumbun; Bambang Ahmad Fauzan (JURNAL MATHEMATIC PAEDAGOGIC, 2023)
Mathematics learning must be facilitated by students' skills in conveying their creative ideas and the teacher's skills needed to provide constructive learning. One of the abilities that can develop students' thinking skills in learning geometry is spatial ability. Mathematical spatial ability pressure in the field of geometry and is important for students to master. The importance of spatial abilities requires students to have good mathematical spatial abilities. Because learning mathematics cannot be separated from geometry, so with good spatial abilities, mathematical abilities will also be good, especially in the field of geometry. The form of an effort to find out students understand geometry material is by using van Hiele's geometric thinking theory so that they are able to overcome students' difficulties in learning geometry. Van Hiele's stages consist of the visualization stage, the analysis stage, the abstraction stage, the deduction stage, and the rigor stage. ). In this study, we wanted to know the spatial abilities of students at the level of visualization (0) and analysis (1) from van Hiele's theory, namely students' initial ability to recognize geometric elements/components.